Unmasking of Brugada syndrome by lamotrigine in a patient with pre-existing epilepsy: A case report with review of the literature - Omer, Hafiz; Omer, Mohamed H.; Alyousef, Abdulmohsen R.; Alzammam, Ali M.; Ahmad, Omar; Alanazi, Haitham A. (Frontiers in Cardiovascular Medicine, 2022)
Brugada syndrome is an inherited cardiac channelopathy arising from mutations in voltage-gated cardiac sodium channels. Idiopathic epilepsy portrays a coalescent underlying pathophysiological mechanism pertaining to the premature excitation of neuronal voltage-gated ion channels resulting in the disruption of presynaptic neurons and the unregulated release of excitatory neurotransmitters. The coexistence of epilepsy and Brugada syndrome may be explained by mutations in voltage-gated ion channels, which are coexpressed in cardiac and neural tissue. Moreover, the incidence of sudden unexpected death in epilepsy has been associated with malignant cardiac arrhythmias in the presence of mutations in voltage-gated ion channels. Lamotrigine is an antiepileptic drug that inhibits neuronal voltage-gated sodium channels, thus stabilizing neural impulse propagation and controlling seizure activity in the brain. However, lamotrigine has been shown to inhibit cardiac voltage-gated sodium channels resulting in a potential arrhythmogenic effect and the ability to unmask Brugada syndrome in genetically susceptible individuals. We are reporting a case of a 27-year-old male patient with a background of presumed idiopathic epilepsy who was initiated on lamotrigine therapy resulting in the unmasking of Brugada syndrome and the onset of syncopal episodes. This case provides further evidence for the arrhythmogenic capacity of lamotrigine and highlights the relationship between epilepsy and Brugada syndrome. In this report, we aim to review the current literature regarding the associations between epilepsy and Brugada syndrome and the impact of lamotrigine therapy on such patients.